2017
DOI: 10.1002/jor.23589
|View full text |Cite
|
Sign up to set email alerts
|

Zirconia phase transformation in retrieved, wear simulated, and artificially aged ceramic femoral heads

Abstract: Zirconia in Zirconia toughened alumina ceramic hip replacements exists in an unstable state and can transform in response to stress giving the material improved fracture toughness. Phase transformation also occurs under hydrothermal conditions such as exist in vivo. To predict the hydrothermal aging that will occur in vivo accelerated aging procedures have been used, but validation of these models requires the study of retrieved hip joints. Here 26 retrievals are analysed to determine the degree of phase trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…For all the other retrievals, stresses related to loading in the central region and to MT phenomenon in the corresponding area were conducive to a zirconia phase transformation of nearly the same extent; in other words, for most retrievals, the two stress conditions did not appear significantly different with regards to the above mentioned transformation, as observed for previously-analysed zirconia retrievals [ 15 ]. From the graphs reported in Figure S3, Supplementary Material , it appears clear that V m increases observed in the centre and MT areas were not related to the follow-up time, in agreement with Parkes et al [ 50 ]. Among the retrievals that showed the most significant increases, some had been implanted for less than one year (#4, #5, #7, #9, #10).…”
Section: Discussionsupporting
confidence: 89%
“…For all the other retrievals, stresses related to loading in the central region and to MT phenomenon in the corresponding area were conducive to a zirconia phase transformation of nearly the same extent; in other words, for most retrievals, the two stress conditions did not appear significantly different with regards to the above mentioned transformation, as observed for previously-analysed zirconia retrievals [ 15 ]. From the graphs reported in Figure S3, Supplementary Material , it appears clear that V m increases observed in the centre and MT areas were not related to the follow-up time, in agreement with Parkes et al [ 50 ]. Among the retrievals that showed the most significant increases, some had been implanted for less than one year (#4, #5, #7, #9, #10).…”
Section: Discussionsupporting
confidence: 89%
“…Each phase contributes to the overall strength of the final composition by the unique way they respond to temperature, liquid media, and stress during manufacturing and use. Retrieval and simulated aging studies have demonstrated these findings both in vivo and in vitro [ 32 , 43 , 49 , [51] , [52] , [53] ]. Current literature suggests zirconia ceramics in vivo undergo greater wear compared with in vitro studies owing to the presence of salts, proteins, and pH of physiologic serum compared with steam autoclaving in artificial aging simulations [ 32 , 34 , 48 , 49 , [51] , [52] , [53] ].…”
Section: Discussionmentioning
confidence: 98%
“…It is validated that this transformation occurs under hydrothermal conditions as well. Comparing monoclinic content and surface roughness, worn areas of the retrieved heads show higher surface roughness than heads that have undergone testing in a hip simulation [ 10 ]. The wear was confirmed as the main reason for the in vivo phase transformation in zirconia, micro-Raman mapping of the fractured articulating surface found the tetragonal-to-monoclinic conversion involved extensively within the region [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Raman experiments demonstrate compositional enhancement of BIOLOX ® delta [ 12 ]. To investigate the changes in material properties of BIOLOX ® delta femoral heads, Raman spectroscopy was used as an effective technique [ 8 , 10 , 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%